THE ROLE OF THE SENTANI CUSTOMARY COUNCIL IN POLICY COMMUNICATION AND AGENDA SETTING IN HANDLING CUSTOMARY LAND CONFLICTS IN JAYAPURA REGENCY - Yudith N.A. Karetji; Henderina Morin; Abner Herry Bajari; Ibrahim Kristofol Kendi (International Journal of Multidisciplinary Reseach, 2026)
This study examines the role of the Sentani Customary Council (DAS) in influencing the public policy agenda in Jayapura Regency through the perspective of policy communication. Indigenous peoples have a strategic position as guardians of traditional values as well as political actors guaranteed by the constitution, the Papua Special Autonomy Law, and Permendagri No. 52 of 2014.Based on Dunn's (2017) public policy theory, the policy process is interactive, involving communication, interests, and power. This research is also based on agenda setting theory (McCombs & Shaw, 1972; Cobb & Elder, 1971) as well as the Multiple Streams model (Kingdon, 2003), which describes how public issues enter the government's agenda through communication and political support.This study uses a descriptive qualitative approach, with data collection through interviews, observations, and documentation studies, which are then analyzed using the analysis model of Miles and Huberman (2014). The results show that watersheds play an important role in framing the issue of land encroachment as a symbol of customary rights through horizontal communication in the community, vertically with the government, and through mass media and social media. This strategy makes cultural issues the government's attention, showing the dynamics of policy networks (Rhodes, 1997) between customary institutions, bureaucracies, NGOs, and civil society. The research concludes that culture-based communication is effective in transforming local issues into politically recognized public policies. Going forward, there is a need for formal recognition of the role of Indigenous Councils, communication capacity building, and collaboration with the media and academics to strengthen local values-based policy governance and indigenous peoples' participation.